2(x-1)+3x=-2

Simple and best practice solution for 2(x-1)+3x=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-1)+3x=-2 equation:


Simplifying
2(x + -1) + 3x = -2

Reorder the terms:
2(-1 + x) + 3x = -2
(-1 * 2 + x * 2) + 3x = -2
(-2 + 2x) + 3x = -2

Combine like terms: 2x + 3x = 5x
-2 + 5x = -2

Add '2' to each side of the equation.
-2 + 2 + 5x = -2 + 2

Combine like terms: -2 + 2 = 0
0 + 5x = -2 + 2
5x = -2 + 2

Combine like terms: -2 + 2 = 0
5x = 0

Solving
5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '5'.
x = 0

Simplifying
x = 0

See similar equations:

| 5x-9x=44-16 | | 4x+160y=136 | | 5x-9=44-16 | | (x+5)(x-5)(4x-8)=0 | | 180=(3x-70) | | 3x-6x=1 | | 64=10x-6 | | -(7+x)= | | a=(5a-6) | | 3(x+2)+4(x-5)=10(x+4) | | -9=(-10) | | 4c-6whenc=3 | | a=(3a-7) | | 6(x+16)= | | (5x+2)(5x+2)=144 | | X-8=-4-26 | | 7x-3x-50=20 | | y-2(y-3)+4= | | 2x+3x-5=50 | | 35z-11=59 | | x=6(2x+1) | | -4-6=5x+9-4x | | 0(8b+4)= | | 26R-3R^2=0 | | 11x+3=2x | | -75=-3x+3 | | 4x-9-9-8x= | | 5j-j= | | X+X+10+2(2X+10)=180 | | 8h-4h= | | -9t+3=-10t | | 2x-(4y-3)+5+-3+-1= |

Equations solver categories